Importance of the Colmation Layer in the Transport and Removal of Cyanobacteria, Viruses, and Dissolved Organic Carbon during Natural Lake‐Bank Filtration. Issue 5 (1st September 2015) - Harvey, Ronald W.; Metge, David W.; LeBlanc, Denis R.; Underwood, Jen; Aiken, George R.; Butler, Kenna; McCobb, Timothy D.; Jasperse, Jay
Abstract : This study focused on the importance of the colmation layer in the removal of cyanobacteria, viruses, and dissolved organic carbon (DOC) during natural bank filtration. Injection‐and‐recovery studies were performed at two shallow (0.5 m deep), sandy, near‐shore sites at the southern end of Ashumet Pond, a waste‐impacted, kettle pond on Cape Cod, MA, that is subject to periodic blooms of cyanobacteria and continuously recharges a sole‐source drinking‐water aquifer. The experiment involved assessing the transport behaviors of bromide (conservative tracer), Synechococcus sp. IU625 (cyanobacterium, 2.6 ± 0.2 µm), AS‐1 (tailed cyanophage, 110 nm long), MS2 (coliphage, 26 nm diameter), and carboxylate‐modified microspheres (1.7 µm diameter) introduced to the colmation layer using a bag‐and‐barrel (Lee‐type) seepage meter. The injectate constituents were tracked as they were advected across the pond water–groundwater interface and through the underlying aquifer sediments under natural‐gradient conditions past push‐point samplers placed at ∼30‐cm intervals along a 1.2‐m‐long, diagonally downward flow path. More than 99% of the microspheres, IU625, MS2, AS‐1, and ∼44% of the pond DOC were removed in the colmation layer (upper 25 cm of poorly sorted bottom sediments) at two test locations characterized by dissimilar seepage rates (1.7 vs. 0.26 m d −1 ). Retention profiles in recovered core material indicated that >82% of the attached IU625 were in the top 3 cm of bottom sediments. The colmation layer was also responsible for rapid changes in the character of the DOC and was more effective (by three orders of magnitude) at removing microspheres than was the underlying 20‐cm‐thick segment of sediment. Core Ideas: More than 98% of cyanobacteria, coliphages, and viruses being tracked were removed in the colmation layer. Modified Lee‐type seepage meters are useful for conducting colloid transport studies at the bottom of lakes. 44% of the pond dissolved organic C transported into the aquifer was removed within the colmation layer. Transport through the colmation layer resulted in a substantive change in dissolved organic C character.